Antimicrobial activity of ozone and NaF-chlorhexidine on early childhood caries - Marcos XIMENES; Mariane CARDOSO; Fernando ASTORGA; Roland ARNOLD; Luiz André PIMENTA; Ricardo de Sousa VIERA
Abstract An early childhood carie (ECC) is an extremely destructive form of tooth decay. The aim of this study was to investigate the action of ozone (O3), and the association of sodium fluoride (NaF) with chlorhexidine (CHX) on bacteria related to ECC. Overnight culture of the bacteria was performed. On exponential phase the suspension was adjusted (101-108 CFU/mL). A drop (10μL) of each concentration of bacteria was applied on sheep blood agar plates and treated with O3 (2, 20, 200, and 2,000 ppm); after 18 hours, recovery analysis of CFU verified the reduction of bacterial activity. For NaF-CHX, sterile 96-well plates were prepared and divided into groups: G1 (150 µL TSB); G2 (20 µL of bacteria + 25 µL CHX + 25 µL NaF); and G3 (150 µL TSB + 20 µL of bacteria + 50 µL water). The plates were verified by analysis of the optical density (0, 12, 14, 16, and 18 hours). The data from O3 test were submitted to ANOVA and Tukey's test (p < 0.05). For the data from NaF-CHX, the ANOVA 2-way and Bonferroni's test (p < 0.05) were used. The number of CFU/mL showed death > 3log10 (99.9%) for all bacteria (ozone ≥ 20ppm), while the combination of NaF-CHX was more effective (p < 0.001) compared to each substance tested alone and the control group. The antimicrobial agents tested were able to inhibit all bacteria tested; O3 seemed to be a good alternative for controlling progression of carious lesions, while the association of NaF-CHX showed to be a good antimicrobial with easy and inexpensive application.